Jacek (Hiacynt) Boratyński – Żydaczów Cupbearer and Lieutenant of the hussars during the Polish-Ottoman wars in the 2nd half of the 17th century. Study of the Profession of the soldier - Hundert, Zbigniew (Saeculum Christianum. Pismo Historyczne, 2021)
Throughout his military career, Jacek Boratyński served in one formation – the winged hussars (husaria). Between 1666 and 1676, he was a companion (towarzysz) in two hussars’ banners (companies): initially in one of Aleksander Michał Lubomirski, Voivode of Krakow, then after 1668 in that of Jan Sobieski, Grand Marshal and Grand Crown (Polish) Hetman (since 1674 King John III). In 1676 he became lieutenant in the hussars’ banner of Jan Gniński, Voivode of Chełmno (since 1682 Crown Vice-Chancellor). In this capacity, as an officer of Polish lancers, he took part in Gniński’s mission to Istanbul (1677–1678) and in the relief operation of Vienna in 1683. He was part of the group of soldiers that were under patronage of Grand Crown Hetman Stanisław Jabłonowski. Between 1676 and 1696 (exact date unknown), Boratyński was one of the commanders in charge of the hetman’s cavalry regiment (pułk). Thanks to military service and patronage, especially of Gniński, he received land office ranks: first Cupbearer (cześnik) of Sanok, then Deputy Cupbearer (podczaszy) of Żydaczów. His military service offers a perfect benchmark for biographical studies of other crown officers of the same rank.